Regulatory T cells: Possible mediators for the anti-inflammatory action of statins. (November 2019) - Shahbaz, Sanaz Keshavarz; Sadeghi, Mahvash; Koushki, Khadije; Penson, Peter E.; Sahebkar, Amirhossein
Graphical abstract: Abstract: Statins beside their main effect on reducing the progression of cardiovascular disease through pharmacological inhibition of the endogenous cholesterol synthesis, have additional pleiotropic effects including antiinflammatory effects mediated through the induction of suppressor regulatory T cells (Tregs). Statin-induced expansion of Tregs reduces chronic inflammation and may have beneficial effects in autoimmune diseases. However, statins could represent a double-edged sword in immunomodulation. Drugs that act by increasing the concentration of Tregs could enhance the risk of cancers, particularly in the elderly and may have adverse effects in neurodegenerative disorders and infectious diseases. In the present paper, we review the experimental studies that evaluate the effects of statins on Treg cells in autoimmune and inflammatory diseases and we discuss potential therapeutic applications of statins in this setting.